A Novel System for Measuring Optical Properties in Arterial Blood of Man - A. Castañeda-Miranda; L. D. L. Vizcaya (Applied Bionics and Biomechanics)
The necessity of man–machine communication has been increasing day by day because of the great number of approaches that help to make human life agile or comfortable. Health is one of the aspects that has generated more interest in recent years. The optical technologies are new technical tools that are being implemented for medical diagnosis and for describing various processes occurring within human blood. These techniques have the virtue of being nondestructive; in addition they have the advantage of remote direction by using an in situ technique, with sensitivity capable of studying the properties of the blood through electromagnetic excitation. A device to obtain the electromagnetic spectrum in the blood has being designed and is presented in this work. This device uses a quartz lamp, emitting electromagnetic radiation between 200 nm and 2200 nm. A model for measuring the light attenuation through the blood is used. By applying a control in the frequency domain, a circuit device is designed. This device uses a database in time domain for its subsequent analysis by Fast Fourier Transformation in order to obtain absorption spectra. The acquisition time is of the order of microseconds, and the system is controlled automatically through accessible software from a personal computer.